The Impact of Shoppable Live Streaming and Brand Trust on Purchase Decisions: The Mediating Role of Purchase Intention in ShopTokopedia Platforms - I Wayan Ryan Kusumatirta; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja; Ni Putu Audi Orlanda; I Gusti Agung Ayu Dian Priskila Chandra; I Wayan Agus Budi Darma; Anak Agung Ayu Pramisanthi Dewi (AIBPM Publisher, 2025)
The rapid growth of e-commerce has reshaped marketing strategies, with shoppable live streams emerging as an innovative medium that merges interactive shopping experiences with real-time entertainment. This study examines the effect of shoppable live streams and brand trust on purchase decisions, with purchase intention positioned as a mediating variable among ShopTokopedia users in Bali, particularly during the platform’s transition from TikTok Shop to ShopTokopedia. Using a quantitative approach, data were collected from 100 respondents and analyzed through Structural Equation Modeling (SEM) with SmartPLS. The findings demonstrate that while shoppable live streams and brand trust significantly influence purchase intention, they do not directly impact purchase decisions. Instead, purchase intention fully mediates the relationship, highlighting its critical role in converting consumer motivation into actual transactions. These results underscore the importance of creating engaging live stream experiences and strengthening consumer trust to drive purchasing behavior. The study contributes original insights into Indonesia’s live commerce ecosystem, offering valuable theoretical implications for consumer behavior research and practical recommendations for businesses aiming to enhance engagement, optimize marketing strategies, and sustain competitiveness in the evolving digital marketplace.